Effect of pure and N-doped carbon quantum dots on the photosynthesis and growth of Brassica juncea (L.) Czern. - Chowmasundaram, Yamuna (2023)
Nitrogen-doped quantum dot (N-CQD) is a novel nanomaterial that has attention in the agriculture field. In this work, the N-CQD was synthesized and characterized. The mechanism of photosynthesis is still not entirely understood, especially for plants growing indoors. The effects of pure and N- CQD on the plants that grow in indoor hydroponic systems are studied. The CQD at various concentrations (ranging from 0-400 ppm) applied via the foliar method toward the leaves of the green mustard plant (Brassica Juncea). A statistical analysis was performed on 54 plant samples (n=54). According to the findings, 150 ppm of both CQD types was determined to be the optimum concentration for promoting plant growth and photosynthesis parameters. The CQD-treated plant dramatically increased the number of leaves produced, leaves area, height, fresh weight, and dry weight compared to the control plant by 28.8%, 40.6%, 34.6%, 161%, and 255%, respectively. The N-CQD treated plant significantly enhanced the number of leaves production, leaves area, height, fresh weight, and dry weight by 79%, 187%, 71.5%, 383%, and 707%, respectively. Furthermore, the CQD treated plant increased transpiration rate, net assimilation, stomatal conductance, and iWUE by 11.9%, 55.7%, 30%, and 28%, respectively. Besides that, N-CQD significantly raised the plant transpiration rate by 28.1%, net assimilation by 114.6%, stomatal conductance by 49.1%, and iWUE by 57.5%. In this study, N-CQD improved the growth and photosynthesis rate of the green mustard plants compared with CQD. The effects of CQD on plants under various light spectrums, including full light spectrum and red/blue light spectrum, have also been studied. The result demonstrates that both CQD types effectively enhanced plant photosynthesis under full light spectrums rather than red/blue light spectrum. For instance, the 150 ppm treated pure CQD plants exposed to the full light spectrum had phiPSII higher than plants exposed to R/B light by 10.2%. Moreover, the 150 ppm treated doped CQD plants exposed to the full light spectrum had phiPSII higher than plants exposed to red/blue light spectrum by 11.2%. The study provides an explanation of how electron transfer works in the CQD/chloroplast complex. This study's findings emphasized the potential of CQD as an efficient method to enhance plant growth and photosynthesis for indoor plants. According to the research, CQD can applied in many plant species and growth environments as an artificial photosynthetic pigment. The innovative methodology created in this study to examine the impacts of CQD under various light spectrums can offer insightful information for maximizing the use of CQD in agriculture.